Основные направления организации воспитательной работы в вузе на современном этапе - Бобкова, Е.А.; Щукина, Т.Н.; Сысолятина, Т.И. (My University, 2013)
In article the questions connected with the main directions to the organization of educational work in higher education institution at the present stage are considered. Younger generation education always was and remains to one of the most important problems of the state. All progressively conceiving people thinking of the future of the country perfectly understand it. Education development in an education system of the Republic of Kazakhstan by right became in recent years one of the priority directions in activity of the Ministry of Education and Science of the Republic of Kazakhstan.